Evaluating patient and physician knowledge of risks and safe use of rivaroxaban: a survey across four countries. Issue 3 (4th March 2022) - Zografos, Laurie; Wolin, Dan; Andrews, Elizabeth; Calingaert, Brian; Balabanova, Yanina; Horvat-Bröcker, Andrea; Tarenz, Christine; Suzart-Woischnik, Kiliana
ABSTRACT: Background: At the request of the European Medicines Agency, a Prescriber Guide and Patient Alert Card were developed to increase awareness and understanding about the initiation of rivaroxaban and potential bleeding risk associated with its use. This study evaluated physician and patient awareness and understanding of key safety messages in these educational materials in three waves. Research design and methods: Three cross-sectional surveys were administered to physicians and one survey was administered to patients (wave 1 only) with recent rivaroxaban experience in France, Germany, Spain, and the United Kingdom. Results: Patient and physician knowledge of key safety information in the educational materials was generally high. Patients' knowledge was high for questions related to bleeding risk (80% responded correctly), indication (96%), consulting their doctor (86%-91%), and informing other physicians they are taking rivaroxaban (95%). Physicians' knowledge was particularly high for questions related to bleeding risk (92%-94% across waves), populations at increased risk of serious side effects (76%-94%), contraindications (70%-92%), and invasive procedures (76%-82%). Conclusions: Among patients and physicians, the highest levels of knowledge were on the most important risks, as expected. The Prescriber Guide and Patient Alert Card were found to be useful sources of information.